Rodolfo Walsh, antecedente de la novela testimonial latinoamericana: sobre la matriz narrativa policial en 'Operación masacre' = Rodolfo Walsh, precedent of the Latin American testimonial novel : on the police story matrix in 'Operación masacre' - Saban, Karen (Pléyade, 2019)
During the short but drastic period of time that was between his first crime short stories gathered in Variaciones en rojo (1953) and his famous testimonial novel, Operación masacre (OM, 1957), an evolution occurred, starting with the respect for the norms of a gender and ending with their transformation through the inauguration of the non-fiction. Being the fruit of a journalistic campaign, the novel abandons the artistic categories of bourgeois art, while the author makes an ideological turn and becomes a committed writer. As the critics identified, thanks to the aesthetic configuration of the verbal material, the real and the fictional are intertwined in a dialectical way, causing the truth to emerge with the value of historical proof. This article, also based on the uncertain generic attribution of the testimony, propose that OM can be considered as the first testimonial novel of Latin American literature, since it contains insipiently the three models that this gender would develop throughout its history: the paradigms of subversion, subalternity and subjectivity. Second, it analyses how OM drives the testimony through a precise form of textual work that, far from untying knots with its police texts, feeds on its narrative matrices.